PENYANDINGAN ADAT KEDALAM HUKUM FIQH (Pemikiran Hukum Islam Prof. Dr. Hazairin, SH) - Adi Yono (Et-Tijarie, 2018)
Hazairin as a reformer of Islamic law in Indonesia better known as the father of bilateral inheritance theory and receptie exit has brought the influence of the era of independence, Islamic law has passed two periods. The First Period is the period of acceptance of Islamic law as a persuasive source in the context of constitutional law, ie a new source of law accepted if it is believed, for example, Islamic law has been included in the formulation of the Jakarta charter as one of the results of BPUPKI sessions. The Second Period is a period in which Islamic law as an authoritative source (lawful source of law) in the constitution, when the Presidential Decree of 5 July 1965 recognizing that the Jakarta Charter embodies the 1945 Constitution.Influence of Dr. Hazairin against the development of Islamic law in Indonesia until now (era of reform) is quite large, where the receptie exit theories have built a formation of "national school" in the meaning of "school" as a real understanding of the Qur'an and Sunnah and "national" Namely Indonesia, with the intention that Islamic law in Indonesia to be "practically" run by his people.Hazairin sebagai tokoh pembaharu hukum Islam di Indonesia yang lebih dikenal sebagai bapak teori kewarisan bilateral dan receptie exit ini telah membawa pengaruh zaman kemerdekaan, hukum Islam telah melewati dua periode. Periode Pertama adalah periode penerimaan hukum Islam sebagai sumber persuasif dalam konteks hukum konstitusi, yaitu sumber hukum yang baru diterima apabila diyakini, contohnya hukum Islam telah masuk dalam rumusan piagam Jakarta sebagai salah satu hasil sidang BPUPKI. Periode Kedua adalah periode dimana hukum Islam sebagai sumber autoritatif (sumber hukum yang telah mempunyai kekuatan hukum) dalam ketatanegaraan, ketika Dekrit Presiden 5 Juli 1965 yang mengakui bahwa Piagam Jakarta menjiwai UUD 1945.Pengaruh Dr. Hazairin terhadap perkembangan hukum Islam di Indonesia sampai sekarang (era reformasi) cukup besar, dimana Bapak teori receptie exit telah membangun suatu bentukan “mazhab nasional” dalam arti “mazhab” sebagai pengertian yang sebenarnya bersandar pada al Qur’an dan Sunnah dan “nasional” yakni Indonesia, dengan maksud agar hukum Islam di Indoensia menjadi “praktis” dijalankan oleh umatnya.Keyword: Customary Law, Fiqh Law, Hazairin